An evaluation of the implementation of cascade training for suicide prevention during the ‘Choose Life’ initiative in Scotland - utilizing Normalization Process Theory - Linda Gask; Nia Coupe; Gillian Green (BMC Health Services Research, 2019)
Abstract Background ‘Cascade training’ or ‘train-the-trainers’ has been widely utilised in the dissemination of information and expertise in health and social care, but with little examination of the work required for optimal delivery. National suicide prevention strategies commonly include such training initiatives. Methods A qualitative study to characterise the work, according to the concepts of Normalization Process Theory, required to disseminate STORM, a model of suicide prevention training across Scotland, and then implement it within organisations. This utilised a cascade style ‘train-the trainers’ intervention delivered as part of the Choose Life suicide prevention strategy in Scotland during 2008–11. Semi-structured interviews were carried out with 19 training facilitators, 30 of their group participants within organisations and 11 local managers within health boards in Scotland. Results Crucial to the process of a cascade training approach to implementing suicide prevention within an organisation was the multi-layered activity of constructing coherence of the intervention at every level in order to prevent dilution of the training. This necessitated collaborative work within and between groups of actors- managers, facilitators and participants. Where facilitators were effectively engaged in their role, confident in their ability to train, supported by supervision and possessed the leadership skills to engage both with participants and their local context to deliver training, there was evidence of both successful delivery and embedding within the organisation. However, there was little systematic evidence of institutional level appraisal- crucial to truly implementing a novel intervention within the system - despite efforts at local managerial engagement. Conclusions Successful cascade or train-the-trainer implementation of an intervention requires extensive collaborative work to take place between and within groups of actors at all levels of an organization from those working at policy level to the ‘coalface’. A priori application of Normalization Process Theory, to specify aims and goals for the necessary work to be carried out between different groups of actors, would assist in embedding a novel working practice at all levels. Future national training strategies for suicide prevention should address what is required to establish a flourishing culture of high-quality skills acquisition and development within healthcare organisations.